ETIKA LINGKUNGAN DAN KINERJA EKONOMI PADA UKURAN GLOBAL REPORTING INITIATIVE-G4 - Temy Setiawan (Universitas Katolik Indonesia Atma Jaya, 2016)
The man–nature relationship has always been ambiguous, nature being seen as both a provider and an enemy. Environmental issue is a phenomena for most profit oriented organizations. They want to earn much profit in short term but they must keep in balance of nature for the future generation. The purpose of this paper is to explore the influence environmental ethics to economic performances directly and using CSR as a mediating variable. This quantitative research use secondary data taken form 68 Indonesian company that published sustainability report for 2014. Quantitative content analysis was be used to process these information and were analyze via PLS SEM. There is no directly influence environmental ethics to economic performance. The role of CSR disclosure using 34 environmental indicators of GRI 4 is very important to explain the indirect influence of environmental ethics to economic performance. This paper explores the link between environmental ethics and economic performance directly and indirectly using CSR disclosure for environmental indicator as a mediating variable.